2014
DOI: 10.1177/00333549141296s404
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Performance Improvement Programs on Preparedness Capacities

Abstract: Objective. In response to public health systems and services research priorities, we examined the extent to which participation in accreditation and performance improvement programs can be expected to enhance preparedness capacities.Methods. Using data collected by the Local Health Department Preparedness Capacities Assessment Survey, we applied a series of weighted least-squares models to examine the effect of program participation on each of the eight preparedness domain scores. Participation was differentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 20 publications
(18 reference statements)
0
6
0
Order By: Relevance
“…Using the PCAS, Davis et al and Bevc et al found decreases in surveillance and investigation and legal preparedness capacities over the 3 survey years, which they attributed to multiple years of funding cuts and job losses specifically for preparedness 10 11 Davis et al found that LHDs that had participated in a performance improvement effort reported significantly greater surveillance and investigation, workforce and volunteer, communication, legal preparedness, exercise and emergency event, and corrective action capacities than comparison LHDs that had not participated in such performance improvement programs 12 . The authors concluded that the PCAS can be useful to assess how well LHDs are performing preparedness capabilities and identify opportunities for program improvement.…”
Section: Resultsmentioning
confidence: 99%
“…Using the PCAS, Davis et al and Bevc et al found decreases in surveillance and investigation and legal preparedness capacities over the 3 survey years, which they attributed to multiple years of funding cuts and job losses specifically for preparedness 10 11 Davis et al found that LHDs that had participated in a performance improvement effort reported significantly greater surveillance and investigation, workforce and volunteer, communication, legal preparedness, exercise and emergency event, and corrective action capacities than comparison LHDs that had not participated in such performance improvement programs 12 . The authors concluded that the PCAS can be useful to assess how well LHDs are performing preparedness capabilities and identify opportunities for program improvement.…”
Section: Resultsmentioning
confidence: 99%
“…Quality improvement outcomes hold particular importance for preparedness capacity, as there is evidence that programs that improve health department performance-such as accreditation-support preparedness capacity. 10 In the face of the COVID-19 pandemic and ongoing cuts to public health and preparedness funding, 15 it is essential that health departments pursue other mechanisms for improving the quality of their preparedness programs. In fact, the PHAB has highlighted examples of accredited health departments applying QI processes to fundamental preparedness functions, such as COVID-19 testing, 16 public health laboratory performance, 17,18 and communicable disease investigations.…”
Section: Discussionmentioning
confidence: 99%
“…8 Furthermore, similar to accreditation, PPHR aims to improve QI processes and confidence in, and credibility and visibility of, health departments. 9 Prior studies found a positive association between participation in state-based health department accreditation or other performance improvement programs and health department preparedness capacities 10 and concluded that accreditation may shield preparedness capacities from consequences of financial and workforce losses and other contextual effects. 11 In addition, PHAB accreditation of state health departments is a measure for the National Health Security Preparedness Index, and the Ready or Not: Protecting the Public's Health From Diseases, Disasters and Bioterrorism report published by Trust for America's Health.…”
mentioning
confidence: 99%
“…One study found that public health department accreditation and other performance improvement programs have a significant and positive effect on preparedness capacities. 51 In another study, research to enhance emergency operations center staff performance yielded more effective teams that enabled a state health department to maintain operations when staffing was severely reduced for a short period. 52,53 Yet another study provided evidence that a state could use a regional preparedness and response team to provide effective training and support to local health departments and save costs.…”
Section: Realization Of the Perrc Program Objectivesmentioning
confidence: 99%